Atypical Chest Pain in ACS: A Trap Especially for Women - Ricci, Beatrice; Cenko, Edina; Varotti, Elisa; Puddu, Paolo E.; Manfrini, Olivia (Current Pharmaceutical Design, 2016)
Not all acute coronary syndromes (ACS) exhibit the classic symptoms of chest pain. The diagnosis of ACS in patients without typical chest pain is often challenging. These patients are at increased risk for delayed or incorrect diagnosis, less aggressive treatment and high in-hospital mortality. The association between diabetes mellitus and absence of chest pain in ischemic heart disease is established. As well, it is known that women, more frequently than men, have atypical presentation. However, there is a lack of standardization in characterizing the population of patients with ACS and atypical presentation. The identification of other factors influencing and/or related with the absence of chest pain in ACS could be helpful for patients’ outcomes. The object of our study was to examine the current literature on the clinical features, other than female gender and diabetes, associated with the atypical presentation of ACS. We found that patients with non-ST-elevation ACS more frequently than patients with ST-elevation myocardial infarction have atypical presentation. Atypical symptoms in aged population are common both among female and male. Subjects with history of comorbidities, specifically heart failure, chronic kidney disease, chronic obstructive pulmonary disease and stroke are less likely to report chest pain as chief complain of ACS.
Keywords: atypical chest pain